Analysis of the utilization of posyandu for the elderly at the Ulin East Health Center in Banjarbaru City - Tamtama, Tatang; Nugroho, Adi; Suhartono, Eko; Husaini, Husaini; Rahman, Fauzie (Institute of Computer Science (IOCS), 2025)
It is important to take the use of elderly posyandu seriously since it is a component of a strategy to enhance the welfare of the elderly through preventative and promotional measures. Just 147 senior persons who utilize health services receive fewer visits from posyandu. This study aims to investigate the relationship between family support, health professional attitudes and knowledge, and accessibility to health services, and the usage of elderly posyandu at Puskesmas Landasan Ulin Timur, Banjarbaru City. A cross-sectional design was used for this investigation. The research subjects consisted of 174 senior adults. In data analysis, chi square and multiple logistic regression tests were employed. The results of the chi square analysis showed the p values for family support (p = 0.000), healthcare professionals' attitudes (p = 0.000), health resource accessibility (p = 0.001), and knowledge (p = 0.000). The knowledge variable and nurse performance had the strongest correlation (Exp(B)=4.456). At Puskesmas Landasan Ulin Timur Banjarbaru City, the use of senior posyandu is associated with family support, health staff attitudes, knowledge, and the availability of health services. Understanding is the most crucial element.